How does cognitive effort influence the tactical behavior of soccer players? - Cardoso, F. S. L.; Garcia-Calvo, T.; Patrick, T.; Afonso, J.; Teoldo, I. (Perceptual and Motor Skills, 2021)
In the present study, we aimed to investigate the association between soccer players` cognitive effort and their tactical behavior. We assessed 52 young male soccer players from a first division Brazilian club, using FUT-SAT to evaluate tactical behavior efficiency and Mobile Eye Tracking-XG software and a video test protocol to measure pupillary behavior and cognitive effort. Following data collection, statistical analyses were performed using the Kolmogorov-Smirnov normality test, and linear regression. We found a high inverse association between cognitive effort and tactical behavior efficiency; players with less cognitive effort during the task displayed higher values of tactical behavior efficiency on the field. We concluded that sustaining less cognitive effort in game situations helped players realize better tactical behavior and enabled better performance.